2009
DOI: 10.1016/j.jdermsci.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topically applied glycolic acid and salicylic acid on ultraviolet radiation-induced erythema, DNA damage and sunburn cell formation in human skin

Abstract: Background-α-Hydroxy acids (αHA) are reported to reduce signs of aging in the skin and are widely used cosmetic ingredients. Several studies suggest that αHA can increase the sensitivity of skin to ultraviolet radiation. More recently, β-hydroxy acids (βHA), or combinations of αHA and βHA have also been incorporated into antiaging skin care products. Concerns have also arisen about increased sensitivity to ultraviolet radiation following use of skin care products containing β-HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
0
35
0
3
Order By: Relevance
“…It has been known that sunburn cells (SBCs) are keratinocytes undergoing apoptosis after UVB irradiation [6,16,17], and GA has effect to induce SBC formation by investigators [5,6]. Kaidbey et al prescribed 10% GA, 6 days per week for 4 weeks, in 16 subjects and found that GA enhanced phototoxicity as revealed by increased SBC formation and lowered the minimal erythema dose (MED) [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been known that sunburn cells (SBCs) are keratinocytes undergoing apoptosis after UVB irradiation [6,16,17], and GA has effect to induce SBC formation by investigators [5,6]. Kaidbey et al prescribed 10% GA, 6 days per week for 4 weeks, in 16 subjects and found that GA enhanced phototoxicity as revealed by increased SBC formation and lowered the minimal erythema dose (MED) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Kaidbey et al prescribed 10% GA, 6 days per week for 4 weeks, in 16 subjects and found that GA enhanced phototoxicity as revealed by increased SBC formation and lowered the minimal erythema dose (MED) [5]. Kornhauser et al enrolled 14 subjects using 10% GA daily on the middle back for 3.5 weeks and subsequently exposed to solar simulated radiation (SSR) with UVB spectrum, and showed that short-term topical application of GA resulted in increased sensitivity of human skin to SSR, measured as an increase in erythema, DNA damage and SBC formation [6]. The existence of sunburn cells may represent an alternative biomarker for UV injury [6,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some study, the enhancement of photosensitivity by glycolic acid is reported [32,33]. In those studies, glycolic acid was applied first, then UV irradiation was done and increase of sunburn cell formation and DNA damages such as cyclobutane pyrimidine dimer (CPD) was observed.…”
Section: [ ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 99%